Sexual violence perpetrated by health professionals - Fávero, Marisalva; Gomes, Vanessa; Campo, Amaia Del; Moreira, Diana; Sousa-Gomes, Valéria (Frontiers in Psychology, 2023)
Sexual violence perpetrated by health professionals concerns any sexual conduct, whether physical or verbal (with or without contact), towards a patient. There has been little scientific study and some disagreements have emerged regarding its definition, which has even been confused with violation of professional boundaries. In this descriptive-exploratory study, we aimed to characterize this phenomenon in the Portuguese context, using a sample of 491 participants who completed an online questionnaire adapted for this study. The results showed that 8.96% of the participants (5.5% indirect victims) suffered sexual violence by a health professional, and the sociodemographic characteristics are very similar to those of sexual violence in other contexts. Thus, after confirming this is not a problem alien to the Portuguese reality, we discuss the practical implications for prevention and intervention with victims.